The Effectiveness of Hydrotherapy in the Management of Rheumatoid Arthritis: A Systematic Review. (16th July 2012) - Al‐Qubaeissy, Khamis Y.; Fatoye, Francis A.; Goodwin, Peter C.; Yohannes, Abebaw M.
Abstract Background Hydrotherapy is frequently indicated for the rehabilitation of patients with rheumatoid arthritis (RA); nevertheless, there has been inadequate appraisal of its effectiveness. The potential benefits of hydrotherapy for patients with RA are to improve and/or maintain functional ability and quality of life. Objectives The aim of this systematic review was to evaluate the effectiveness of hydrotherapy in the management of patients with RA. Method AMED, CINAHL, EMBASE, MEDLINE, PubMed, Science Direct and Web of Science were searched between 1988 and May 2011. Keywords used were rheumatoid arthritis, hydrotherapy, aquatic physiotherapy, aqua therapy and water therapy. Searches were supplemented with hand searches of references of selected articles. Randomized controlled trials were assessed for their methodological quality using the Physiotherapy Evidence Database (PEDro) scale. This scale ranks the methodological quality of a study scoring 7 out of 10 as 'high quality', 5–6 as 'moderate quality' and less than 4 as 'poor quality'. Results Initially, 197 studies were identified. Six studies met the inclusion criteria for further analysis. The average methodological quality for all studies was 6.8 using the PEDro scale. Most of the studies reported favourable outcomes for a hydrotherapy intervention compared with no treatment or other interventions for patients with RA. Improvement was particularly noted in reducing pain, joint tenderness, mood and tension symptoms, and increasing grip strength and patient satisfaction with hydrotherapy treatment in the short term. Conclusions There is some evidence to suggest that hydrotherapy has a positive role in reducing pain and improving the health status of patients with RA compared with no or other interventions in the short term. However, the long‐term benefit is unknown. Further studies are needed. Copyright © 2012 John Wiley & Sons, Ltd.